Efecto de la criopreservación en el potencial de membrana plasmática en espermatozoides de alpaca (Vicugna pacos) - Perez Ramos, Jefry (2024)
Membrane potential is the electrical difference between the inside and outside of a cell, and depolarization is the reduction of the negative value of this potential. This study aimed to determine the state of the plasma membrane potential of alpaca spermatozoa after cryopreservation, using fluorescence intensity as a measure. In total, 32 epididymal sperm samples subjected to a standard cryopreservation protocol were analysed. Each sample was evaluated before and after the process. The fluorochrome DISBAC2(3) was used at 15 µm for 30 min and 12 µM propidium iodide (PI) at 37 °C for 10 min to analyse membrane depolarization and viability, respectively. Measurements were performed with a flow cytometer containing an image analyser, using a 488 nm excitation laser and the detection channels Ch03 and Ch05 for DisBAC2(3) and PI, respectively. The mean fluorescence intensity of DisBAC2(3) in fresh live spermatozoa was 3176 ± 1398, while in thawed spermatozoa it was 2356 ± 1206 (p<0.05). Results suggest that cryopreservation, on average, reduces the fluorescence intensity of DisBAC2(3), which can be interpreted as a hyperpolarization of the plasma membrane after thawing.